Heavy-light mesons from a flavour-dependent interaction - Gao, Fei; Miramontes, Angel S.; Papavassiliou, Joannis; Pawlowski, Jan M. (Physics letters, 2025)
We introduce a new framework for the physics of heavy-light mesons, whose key element is the effective incorporation of flavour-dependent contributions into the corresponding bound-state and quark gap equations. These terms originate from the fully-dressed quark-gluon vertices appearing in the kernels of these equations, and provide a natural distinction between “light” and “heavy” quarks. In this approach, only the classical form factor of the quark-gluon vertex is retained, and is evaluated in the so-called “symmetric” configuration. The standard Slavnov-Taylor identity links this form factor to the quark wave-function, allowing for the continuous transition from light to heavy quarks through the mere variation of the current quark mass in the gap equation. The method is used to compute the masses and decay constants of specific pseudoscalars and vector heavy-light systems, showing good overall agreement with both experimental data and lattice simulations.
Online verfügbar: 10. März 2025, Artikelversion: 12. März 2025
Gesehen am 18.08.2025